(untitled) - Hanna Järvenpää; Ari Haaranen; Mari Kangasniemi (University of Ostrava, 2024)
Aim: The centralization of Finnish maternity services can mean longer journeys when women are in labor. The aim of this study was to describe women's experiences of having an unplanned out-of-hospital delivery (OHD) and to produce a deeper understanding of how to support them when this happens. Design: Qualitative descriptive study design with narrative inquiry method. Methods: Individual interviews were carried out with 15 women who had an unplanned OHD and the data were analyzed using a narrative method. Results: Three narratives described the women's experiences of an unplanned OHD with a common plot being their sense of control. In the first narrative, a sense of control was maintained; in the second, the sense of control fluctuated; and the third narrative centered on a loss of control. All the narratives were related to the women's experiences of what was happening to their body, the people around them during delivery, and the situation after the childbirth. Conclusion: Having an unplanned OHD forced women to reconsider their preconceptions and expectations of childbirth and focus on how to handle the situation at hand. A key factor was the sense of control they felt while giving birth, which should be considered a core principle in maternity care practices, from antenatal care to delivery.